Role of rituximab in treatment of patients with primary central nervous system lymphoma: a retrospective analysis of the Czech lymphoma study group registry. Issue 12 (1st December 2016) - Mocikova, Heidi; Pytlik, Robert; Sykorova, Alice; Janikova, Andrea; Prochazka, Vit; Vokurka, Samuel; Berkova, Adela; Belada, David; Campr, Vit; Buresova, Lucie; Trneny, Marek; ,
Abstract: We have investigated whether the addition of rituximab to methotrexate, procarbazine, vincristine, radiotherapy and cytarabine was associated with improved outcome of primary central nervous system lymphomas (PCNSL). Of 164 patients, 49 received rituximab. Median age was 63 years, median Karnofsky performance score (KPS) was 60 and median follow-up of living patients was 59.5 months. 1- and 2-year PFS were 49.7 and 37.9%, 1- and 2-year OS were 57.0 and 45.3%. Median progression-free survival (PFS), but not overall survival (OS) was significantly better for patients treated with rituximab (22.9 vs. 10.9 months, p  = 0.037). In multivariate analysis, age ≤70 years and KPS ≥90 were predictive for PFS and OS, rituximab was an independent prognostic factor for PFS only. In landmark analyses, rituximab was not found beneficial for long-term survivors and no group particularly benefited from rituximab. In conclusion, addition of rituximab was associated with improved PFS, but not OS in this unselected cohort of PCNSL patients.